The pioneering contributions of Alexander Von Frantzius to the cartography of Costa Rica - Hilje Quirós, Luko (2024)
Arriving in Costa Rica in 1854, the German physician and naturalist, Alexander von Frantzius, worked in various disciplinary fields. In this regard, in 1869 he published in German the article State of Our Knowledge on the Geography and Cartography of Costa Rica, along with a map of a large portion of the country. However, when the article was translated into Spanish, in 1919, the map was involuntarily omitted. In this article, his text is transcribed and complemented with abundant explanatory notes, in addition to inserting the map and comparing it with another one that he made in 1861, referring to the northern region of the country. In fact, both have great historical value, as they represent the first formal attempts to map the country based on locally-generated knowledge. This, in turn, makes von Frantzius the first promoter of cartography in Costa Rica.